The Motive for Using @schfess Twitter Account to Meet the Followers’ Information Needs - Selviana, Selviana; Wanastri, Prisinta (Librarianship in Muslim Societies, 2023)
Currently, social media is widely used as a source of information by its users to meet their information needs. This study aims to determine the motives of followers to use the Twitter account @schfess as a means of fulfilling their information needs. This study uses quantitative descriptive research methods with survey data collection techniques, namely distributing questionnaires to 100 respondents who are followers of the @schfess Twitter account. The data analysis technique used is descriptive analysis of the percentage. The results show that there are four types of motives that encourage someone to use social media with the information motive having the highest average value of 3.52 which is included in the "Very High" category, integrity motives and social interaction of 3.09 which are included in the "High" category, entertainment motives of 3.00 which were included in the "High" category, and personal identity motives had the lowest average score of 2.95 which was included in the "High" category. Based on the results of the study, it can be concluded that the majority of followers use the Twitter account @schfess to obtain the latest information about education, as a learning tool, and obtain guidance or advice on various problems of school life. Therefore, the researcher hopes that the @schfess Twitter account can increase supervision over the dissemination of information, especially regarding education, so that followers can continue to use the @schfess Twitter account. This research can add insight and knowledge about the use of social media, such as students who use social media like Twitter as a means of fulfilling additional information needs, especially about education.